ENVIRONMENT OF THE MUSEUM WORKERS' MEMORY (American Journal of Research in Humanities and Social Sciences, 2025)
The article is devoted to perpetuating the memory of museum figures who have made a significant contribution to the development of museum business and the preservation of cultural heritage. The work examines various methods and forms of memorialization, such as the establishment of monuments, the creation of plaques, the organization of exhibitions, as well as the publication of scientific papers and documentaries about the life and work of these figures. Special attention is paid to the role of museums in preserving historical memory and shaping cultural heritage through personalized exhibitions and events dedicated to prominent figures of museum science.